Assembling the Brazilian flora: overview of Leguminosae diversity The Brazil Flora Group – Leguminosae (Recommended citation: BFG - Leguminosae) - Pires Morim, Marli; Ranzato Filardi, Fabiana Luiza; Bagnatori Sartori, Angela Lucia B.; Fragomeni Simon, Marcelo; Vieira Iganci, Joao Ricardo; Lewis, Gwilym P.; Cavalcante de Lima, Haroldo; Nic Lughadha, Eimear; Ferreira Fernandes, Moabe; Paganucci de Queiroz, Luciano; Cardoso, Domingos; Morales, Matias; et al. (Springer, 2024)
Over the last two centuries, since the treatment of Leguminosae in Flora Brasiliensis, many new legume species and genera have been described, adding to the accumulated body of knowledge on species’ circumscriptions and distribution, published in monographs, taxonomic revisions and regional floristic treatments of specific Brazilian phytogeographic domains. The Flora do Brasil 2020 project was a collaborative effort conducted between 2008 and 2020 to meet the targets set by the Global Strategy for Plant Conservation, an initiative of the Convention on Biological Diversity. The project aimed to inventory and revise the taxonomy of all plant species in Brazil, including Leguminosae. The monograph of the legume family was carried out by a team of 102 taxonomists (10% of the project’s total), who worked towards updating and verifying the taxonomy of these plants in an online platform. Information on the life forms, substrate, endemism level, and geographical distribution for all accepted taxa were provided, alongside morphological descriptions, identification keys, images of herbarium specimens and field photographs. In this work, we have extracted from the Flora do Brasil 2020 project the legume data consolidated on December 31st, 2020 to provide an overview of the species diversity of Leguminosae in Brazil and its distribution across phytogeographic domains. The results revealed that the family is represented by 220 genera, of which 19 are endemic, and a total of 2901 species (1576 endemic). After fully monographing 210 genera (95%), we showcased Leguminosae as the most diverse family in the country, representing 6% of the total vascular plant species documented in the Flora do Brasil 2020. The species are found in all phytogeographic domains, exhibiting a wide range of life forms. The Mata Atlântica and Caatinga domains together contain the largest number of endemic legume genera in Brazil, most of them monospecific. A discussion on the conservation status of the Brazilian legume species is also provided. Knowledge of the Brazilian flora is continuously advancing, particularly with regards to Leguminosae, demanding regular taxonomic and nomenclatural updates. Current collaborations have greatly improved our understanding of legume diversity and distribution, providing evidence to inform conservation prioritization and action for the Leguminosae in Brazil’s megadiverse flora.